The Impact of Political Discourse in Corporate Social Responsibility Strategies in a Post Conflict Environment: Presidential Speeches and CSR Corporate Reports in Colombia - Olano Carrillo, Carlos Andres (2015)
The present dissertation addresses the complexity of Corporate Social Responsibility in a peace building and post conflict environment, focused on the on-going peace talks between the Colombian government and the FARC guerrilla.